Alumina-coated ternary positive electrode material and method for preparing waste ternary batteries
By performing multi-step processing and leaching separation of waste ternary batteries, alumina-coated ternary cathode material is prepared, which solves the problems of long processes, large environmental pollution and impurities in the existing lithium battery recycling technology, and achieves efficient recycling and Excellent electrochemical properties.
Patent Information
- Application Number
- CN202211084253.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-06
AI Technical Summary
The existing lithium battery recycling technology has problems such as long process, large environmental pollution, and the prepared ternary cathode materials contain impurities, which affect the electrochemical performance.
By discharging, crushing, cracking and sorting the waste ternary battery, leaching is performed using a mixture of ammonia and hydrogen peroxide, then filtering is separated and heated and evaporated to de-ammonia, and finally precipitated in the alkali solution and supplemented with lithium source and hydrogen Alumina colloids are prepared by ball milling, spray drying and calcining.
It has achieved efficient recycling of nickel, cobalt and manganese, with high utilization rate of raw materials, low cost and low environmental pollution, excellent electrochemical performance, few impurities, high stability and good safety.
Smart Images

Figure CN115472942B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery recycling, and in particular to an alumina-coated ternary positive electrode material and a method for preparing waste ternary batteries. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long service life, high safety, and low environmental pollution. Since the commercialization of lithium-ion batteries, after 30 years of development, lithium-ion batteries have been widely used in 3C, energy storage, electric vehicles and other fields. The lithium battery market segments are mainly power lithium batteries, energy storage lithium batteries and consumer lithium batteries. Among them, the downstream application areas of power batteries are mainly new energy vehicles, the downstream application areas of energy storage batteries are mainly power systems, and the downstream application areas of consumer batteries are mainly consumer electronics such as mobile phones.
[0003] The positive electrode materials of power lithium batteries in the lithium battery market are mainly lithium iron phosphate and ternary positive electrode materials. In order to save resources, lithium batteries are usually recycled. Currently, the recycling of lithium batteries in the market is mainly divided into wet method and fire method.
[0004] The advantage of the wet method is that it can purify and prepare high-purity lithium carbonate, ternary precursors, etc., but its disadvantages are long process, high wastewater treatment costs, and greater impact on the environment. The advantage of the fire method is that the process is short and can repair ternary positive electrode materials, but the prepared ternary positive electrode materials contain impurities such as aluminum and copper, which cannot guarantee the stability of the material and the safety of the battery, thus affecting the electrochemical performance of the battery. Summary of the invention
[0005] In view of this, the present application provides an alumina-coated ternary positive electrode material and method for preparing waste ternary batteries. The method has high raw material utilization, high recovery rate, low cost, low environmental pollution, and the resulting product has good electrochemical properties.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions:
[0007] In a first aspect, the present application provides a method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries, comprising the following steps:
[0008] S1. Discharge, crush, crack and sort the used ternary batteries to obtain crude black powder, and then remove magnetism and impurities;
[0009] S2. Leaching the demagnetized and impurity-removed crude black powder using a mixture of aqueous ammonia and hydrogen peroxide, and then performing filter press separation to obtain a first black powder residue and a first filtrate;
[0010] S3. heating the first filtrate, evaporating and deammoniating to obtain recovered ammonia water and copper hydroxide, and adding the recovered ammonia water as a raw material to step S2 for recycling; leaching the first black powder residue with a mixture of hydrogen peroxide and an organic acid at a pH value of 3-4, and then performing filter press separation to obtain a second black powder residue and a second filtrate;
[0011] S4. Add alkaline solution to the second filtrate to precipitate hydroxides of aluminum, calcium and magnesium; the second black powder filter residue contains nickel, cobalt, manganese and lithium. After measuring the nickel, cobalt, manganese and lithium contents in the second black powder filter residue, add lithium source and aluminum hydroxide colloid to the second black powder filter residue to obtain a mixed material, so that the molar ratio of the sum of the moles of manganese, cobalt and nickel in the mixed material to the molar ratio of the lithium source and aluminum hydroxide colloid is 1: (1.05-1.06): (0.01-0.02); the mixed material is ball-milled, spray-dried, calcined and air-flow-pulverized to obtain an alumina-coated ternary positive electrode material.
[0012] Preferably, in step S1, the cracking temperature is 500-600°C, and the cracking atmosphere is a nitrogen atmosphere.
[0013] Preferably, in step S2, the mass ratio of ammonia water, black powder and hydrogen peroxide is (0.2-0.4):1:(0.1-0.2), wherein the concentration of ammonia water is 10-16%.
[0014] Preferably, in step S2, the leaching temperature is 80-100°C and the leaching time is 4-8h;
[0015] Preferably, in step S3, the temperature for evaporation and deamination is 100-110° C., and the reaction time is 2 h.
[0016] Preferably, in step S3, the organic acid is one or more of acetic acid, citric acid, tartaric acid, oxalic acid, malic acid, ascorbic acid benzoic acid, salicylic acid, and caffeic acid.
[0017] Preferably, in step S4, the ball milling is wet milling, the ball milling medium is one or more of anhydrous ethanol and methanol, the ball milling time is 1-3 hours, and the particle size D50 of the mixed material after ball milling is 1.0-3.0 μm.
[0018] Preferably, in step S4, the spray drying temperature is 180-220° C., and the particle size D50 of the mixed material after spray drying is 5-20 μm.
[0019] Preferably, in step S4, the calcination conditions are as follows: the calcination atmosphere is oxygen or air, the calcination temperature is 700-1000° C., and the calcination time is 4-15 hours.
[0020] Preferably, in step S4, the lithium source is one or more of lithium hydroxide and lithium carbonate.
[0021] In a second aspect, the present application provides an alumina-coated ternary positive electrode material.
[0022] The beneficial effects of this application are as follows:
[0023] 1. This application uses waste ternary batteries to recycle nickel, cobalt and manganese as raw materials for ternary positive electrode materials. The method has a recovery rate of more than 99% for nickel, cobalt and manganese, a high raw material utilization rate, and a wide range of utilization of the obtained battery shells, aluminum, copper and other by-products. The raw materials are easy to obtain, the cost is low, the environmental pollution is small, the impurity removal process is small, and the equipment requirements are low, which is suitable for large-scale production;
[0024] 2. The alumina-coated ternary positive electrode material prepared in this application has few impurities, high stability, good safety, and excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the process route of the present invention;
[0026] Figure 2 This is the SEM image of the ternary positive electrode material of Example 3;
[0027] Figure 3 XRD of ternary cathode material prepared for Example 3; DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] The present application provides a method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries, comprising the following steps:
[0030] S1. The waste ternary batteries are discharged, charged and crushed, high-temperature cracked and sorted to obtain a mixture of black powder crude products containing impurities, and then the electromagnetic demagnetizer is used to remove the iron and magnetic foreign matter brought by the equipment. In this step, the black powder crude product contains the raw materials of the ternary positive electrode materials nickel, cobalt and manganese, as well as the negative electrode materials graphite, copper particles and aluminum particles. The specific steps are as follows: the waste ternary batteries are discharged using a battery cell detection cabinet, and then placed in a charged crusher for crushing. At the same time, nitrogen is introduced into the charged crusher to prevent explosion when the battery is crushed. After charged crushing, it enters a high-temperature rotary kiln to crack at 500-600℃ and nitrogen is introduced to protect the decomposition of the broken battery electrolyte, diaphragm, binder, etc. After the above operations, the ternary positive electrode materials nickel, cobalt and manganese, negative electrode materials graphite, copper foil, aluminum foil and battery byproduct solution diaphragm, battery shell, etc. are obtained, and then the black powder crude product is obtained through airflow sorting and gravity sorting steps.
[0031] S2. The black powder crude product after demagnetization and impurity removal is leached with a mixture of ammonia water and hydrogen peroxide to leach the copper particles in the above mixture, and then the mixture is separated by filter pressing to obtain a first black powder residue and a first filtrate, wherein the leaching temperature is 80-100°C, the leaching time is 4-8h, the mass ratio of ammonia water, black powder and hydrogen peroxide is (0.2-0.4):1:(0.1-0.2), wherein the concentration of ammonia water is 10-16%, and in this step, the first filtrate is a copper complex Cu(NH 3 ) 4 (OH) 2 The first black powder filter residue includes black powder containing nickel, cobalt and manganese, raw materials of ternary positive electrode materials, and graphite, anode material, as well as aluminum particles, and calcium and magnesium impurities introduced from the environment. After the above steps, ammonia water and hydrogen peroxide are used as leaching alkali to avoid the introduction of impurity ions into the solution. No additional impurity removal process is required, which can reduce costs and improve economic benefits.
[0032] S3. The first filtrate is heated and deammonified by evaporation at 100-110°C for 2h to obtain recovered ammonia water and copper hydroxide precipitate, and the recovered ammonia water is added with pure water to prepare 10-16% ammonia water and then added as a raw material to step S2 for recycling, and copper hydroxide can be used as a commercial product;
[0033] Under the condition of pH value of 3-4, the first black powder filter residue is leached with a mixture of hydrogen peroxide and an organic acid, and then filtered to obtain a second black powder filter residue and a second filtrate. In this step, the second black powder filter residue contains black powder of nickel, cobalt and manganese, a raw material of the ternary positive electrode material, and graphite, a negative electrode material. The second filtrate is a solution containing calcium, magnesium and aluminum ions obtained by acid-base oxidation reaction; the organic acid is one or more of acetic acid, citric acid, tartaric acid, oxalic acid, malic acid, ascorbic acid benzoic acid, salicylic acid and caffeic acid, and other impurity ions such as sulfate and chloride ions will not be introduced. At the same time, the dilute organic acid will not react with nickel, cobalt and manganese, thereby reducing the leaching loss of nickel, cobalt and manganese. A pH value less than 3.0 will cause the loss of nickel, cobalt and manganese, and a pH value greater than 4.0 will cause incomplete washing of impurity ions;
[0034] S4. Adding an alkaline solution such as a 32% sodium hydroxide solution to the second filtrate to precipitate aluminum, calcium and magnesium hydroxides, wherein the aluminum hydroxide can be used as a coating raw material;
[0035] The contents of nickel, cobalt and manganese in the second black powder filter residue are detected, and a lithium source and aluminum hydroxide colloid are added to the second black powder filter residue to obtain a mixed material, so that the molar ratio of the sum of the moles of manganese, cobalt and nickel in the mixed material to the lithium source and aluminum hydroxide colloid is 1: (1.05-1.06): (0.01-0.02), the mixed material is spray-dried and calcined after ball milling, and after calcination, the negative electrode material graphite is decomposed into carbon dioxide, the calcined clinker is crushed by an air flow mill, and then mixed and batched, iron-removed and vacuum-packaged to obtain a single crystal ternary positive electrode material and coated with alumina, that is, an alumina-coated ternary positive electrode material.
[0036] The coating principle of this scheme is as follows: in view of the defects of alumina-coated ternary positive electrode materials in the prior art, such as uneven alumina coating, excessive thickness, water phase introduction, and unstable interface structure, the present invention uses a gel method and an organic solvent as a ball milling medium to effectively disperse aluminum hydroxide colloid, and decomposes aluminum hydroxide by high-temperature sintering to form a single crystal ternary positive electrode material coated with alumina, providing a method for alumina-coated ternary positive electrode materials that is effective, highly controllable, fast, and can be mass-produced, overcoming the defects of uneven alumina coating, excessive thickness, water introduction, and unstable interface structure in the preparation of alumina-coated ternary positive electrode materials by the traditional hydroxide precipitation method. The coated alumina is a ceramic type, and the HF in the battery system can be consumed by forming Al-OF and Al-F layers, which can effectively improve the cycle performance and safety of the battery.
[0037] In step S4, the ball milling is wet milling, the ball milling medium is one or more of anhydrous ethanol and methanol, so that the material accounts for 30-60% of the ball milling medium, the ball milling time is 1-3h, the particle size D50 of the mixed material after ball milling is 1.0-3.0μm, the spray drying temperature is 180-220°C, the particle size D50 of the mixed material after spray drying is 5-20μm, the calcination conditions are, the calcination atmosphere is oxygen or air, the calcination temperature is 750-900°C, and the calcination The time is 6-13h. The calcination temperature is determined according to the proportion of nickel in nickel, cobalt and manganese. The medium nickel (5 series and 6 series ternary positive electrode materials) is 900°C, and the high nickel (7 series, 8 series and 9 series ternary positive electrode materials) is 750°C. The calcination time is determined according to the particle size after spray drying. For example, the calcination time of D50: 10-12μm is 6 hours, and the calcination time of D50: 3-5μm is 13 hours. The calcination atmosphere is determined according to the proportion of nickel in nickel, cobalt and manganese. Air is introduced into the medium nickel and oxygen is introduced into the high nickel.
[0038] In step S4, the lithium source is one or more of lithium hydroxide and lithium carbonate. The raw materials are common and easily available, low in price, high in economic benefits, and suitable for large-scale production.
[0039] At the same time, the present application provides an alumina-coated ternary positive electrode material.
[0040] Through the above-mentioned processing steps, the alumina-coated ternary positive electrode material obtained in the present application has few impurities, and can effectively remove impurity elements such as copper, aluminum, and magnesium, so that the purity of the product raw material is high. Through the preliminary decomposition of the raw materials in step S1, the selection of the leaching solution in steps S2 and S3, and the limitation of the leaching conditions, the recovery rate of the raw materials nickel, cobalt, and manganese of the ternary positive electrode material in the present application is high and the loss is small, which provides a good foundation for the subsequent preparation of the stability of the alumina-coated ternary positive electrode material.
[0041] The method for preparing alumina-coated ternary positive electrode materials in the prior art is to directly coat the finished NCM with alumina while regenerating and repairing the ternary positive electrode materials. The product advantage of this solution is that the raw materials come from waste ternary lithium-ion batteries, the process flow is simple, the coating is uniform by ball milling, and the cost is low. Since the manganese, cobalt and nickel raw materials obtained by the recovery step are different from the ternary materials in the prior art in terms of particle size, surface morphology and raw material particle size, compared with directly coating the ternary positive electrode materials with alumina, the coating density, uniformity and continuity of this application are better, and different process methods are used for different waste ternary battery raw materials to ensure good product consistency and low cost.
[0042] The present solution is further described below with reference to embodiments.
[0043] Example 1
[0044] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries comprises the following steps:
[0045] S1. Discharge the used ternary 523 type battery in a battery testing cabinet to <3.0V, crush it with electricity, crack it under a nitrogen atmosphere at 600℃, and obtain a crude black powder by air flow sorting, gravity sorting, and optical sorting, and then remove magnetic impurities. The crude black powder in this step includes ternary positive electrode material raw materials, negative electrode material graphite, and copper and aluminum impurities. After the above steps, the content of ternary positive electrode material raw materials in copper foil after sorting is less than 0.1%, the content of ternary positive electrode material raw materials in aluminum foil is less than 0.1%, the copper content in the crude black powder is less than 2%, and the aluminum content is less than 4%;
[0046] S2. Leaching the demagnetized and impurity-removed mixture at 80° C. for 8 h using a mixture of ammonia water and hydrogen peroxide, wherein the mass ratio of ammonia water, black powder, and hydrogen peroxide is 0.2:1:0.2, wherein the concentration of ammonia water is 15%, and then performing filter press separation to obtain a first black powder filter residue and a first filtrate. After the above steps, the copper content in the first black powder filter residue is less than 0.01%, and the proportion of manganese, cobalt, and nickel is high, providing a basis for subsequent high recovery rate;
[0047] S3. The first filtrate is heated at 100°C for 2h to form copper hydroxide precipitation, and the volatilized ammonia is condensed through an ammonia absorption tower and absorbed by pure water to 15% to obtain recovered ammonia, which is then added as a raw material to step S2 for recycling;
[0048] The hydrogen peroxide and the first black powder filter residue are mixed in a mass ratio of 0.2:1, heated to 85° C., and 20% citric acid is added to adjust the pH to 3, leached, and then filtered to obtain a second black powder filter residue and a second filtrate;
[0049] S4. Add 32% sodium hydroxide solution to the second filtrate to adjust the pH to 12, and precipitate aluminum, calcium and magnesium hydroxides;
[0050] The contents of nickel, cobalt and manganese in the second black powder filter residue are detected, and the second black powder is obtained as a medium nickel product. Lithium carbonate and aluminum hydroxide colloid are added to the second black powder filter residue to obtain a mixed material, so that the molar ratio of the sum of the moles of manganese, cobalt and nickel in the mixed material to the lithium source and the aluminum hydroxide colloid is 1:1.05:0.02. The mixed material is added as a ball milling medium for wet grinding, the solid content is 40%, the ball milling time is 3h, the particle size D50 of the mixed material after ball milling is 2.0-3.0μm, the material after ball milling is spray dried, the spray drying temperature is 200℃, the particle size D50 of the mixed material after spray drying is 12μm, the dried material is calcined, the calcination atmosphere is air, the calcination temperature is 900℃, the calcination time is 6h, the air intake pressure is 0.3MPa, and then it is air flow crushed to obtain the alumina coated ternary positive electrode material (NCM).
[0051] Example 2
[0052] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries comprises the following steps:
[0053] S1. The used ternary 523 type battery is discharged in a battery testing cabinet to <3.0V, crushed with electricity, cracked under a nitrogen atmosphere at 550°C, and sorted by air flow, gravity, and light to obtain a crude black powder product, and then demagnetized and impurities are removed. The crude black powder product in this step includes ternary positive electrode material raw materials, negative electrode material graphite, and copper and aluminum impurities;
[0054] S2. The mixture after demagnetization and impurity removal is leached at 80° C. for 8 h using a mixture of ammonia water and hydrogen peroxide, wherein the mass ratio of ammonia water, black powder and hydrogen peroxide is 0.3:1:0.1, wherein the concentration of ammonia water is 12%, and then the mixture is separated by filter pressing to obtain a first black powder residue and a first filtrate;
[0055] S3. The first filtrate is heated at 110°C for 2h to form copper hydroxide precipitation, and the volatilized ammonia is condensed through an ammonia absorption tower and absorbed by pure water to 10-16% to obtain recovered ammonia, which is then added as a raw material to step S2 for recycling;
[0056] The hydrogen peroxide and the first black powder filter residue are mixed in a mass ratio of 0.2:1, heated to 80° C., and 20% citric acid is added to adjust the pH to 4, leached, and then filtered to obtain a second black powder filter residue and a second filtrate;
[0057] S4. Add 32% sodium hydroxide solution to the second filtrate to adjust the pH to 12, and precipitate aluminum, calcium and magnesium hydroxides;
[0058] Lithium carbonate and aluminum hydroxide colloid are added to the second black powder filter residue to obtain a mixed material, so that the molar ratio of the sum of the molar amounts of manganese, cobalt and nickel in the mixed material to the lithium source and aluminum hydroxide colloid is 1:1.05:0.02, the mixed material is added as a ball milling medium for wet grinding, the solid content is 50%, the ball milling time is 3 hours, the particle size D50 of the mixed material after ball milling is 2.0-3.0μm, the material after ball milling is spray dried, the spray drying temperature is 200°C, the particle size D50 of the mixed material after spray drying is 12μm, the dried material is calcined, the calcination atmosphere is air, the calcination temperature is 900°C, the calcination time is 6 hours, the air intake pressure is 0.3MPa, and then it is air flow crushed to obtain the alumina-coated ternary positive electrode material (NCM).
[0059] Example 3
[0060] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries comprises the following steps:
[0061] S1. The waste ternary 811 type battery is discharged in a battery testing cabinet to <3.0V, crushed with electricity, cracked under a nitrogen atmosphere at 550°C, and sorted by air flow, gravity, and light to obtain a crude black powder, and then demagnetized and impurities are removed. The crude black powder in this step includes ternary positive electrode material raw materials, negative electrode material graphite, and copper and aluminum impurities;
[0062] S2. The mixture after demagnetization and impurity removal is leached at 80° C. for 6 h using a mixture of ammonia water and hydrogen peroxide, wherein the mass ratio of ammonia water, black powder and hydrogen peroxide is 0.3:1:0.1, wherein the concentration of ammonia water is 12%, and then the mixture is separated by filter pressing to obtain a first black powder residue and a first filtrate;
[0063] S3. The first filtrate is heated at 105°C for 2h to form copper hydroxide precipitation, and the volatilized ammonia is condensed through an ammonia absorption tower and absorbed by pure water to 12% to obtain recovered ammonia, which is then added as a raw material to step S2 for recycling;
[0064] The hydrogen peroxide and the first black powder filter residue are mixed in a mass ratio of 0.2:1, heated to 80° C., and 20% citric acid is added to adjust the pH to 3.0, leached, and then filtered to obtain a second black powder filter residue and a second filtrate;
[0065] S4. Add 32% sodium hydroxide solution to the second filtrate to adjust the pH to 12, and precipitate aluminum, calcium and magnesium hydroxides;
[0066] Lithium hydroxide and aluminum hydroxide colloid are added to the second black powder filter residue to obtain a mixed material, so that the molar ratio of the sum of the molar amounts of manganese, cobalt and nickel in the mixed material to the lithium source and aluminum hydroxide colloid is 1:1.05:0.01, the mixed material is added as a ball milling medium for wet grinding, the solid content is 40%, the ball milling time is 3 hours, the particle size D50 of the mixed material after ball milling is 1.0-2.0μm, the material after ball milling is spray dried, the spray drying temperature is 200℃, the particle size D50 of the mixed material after spray drying is 10μm, the dried material is calcined, the calcination atmosphere is oxygen, the calcination temperature is 750℃, the calcination time is 6h, the air intake pressure is 0.3MPa, and then it is air flow crushed to obtain the alumina-coated ternary positive electrode material (NCM).
[0067] Example 4
[0068] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries comprises the following steps:
[0069] S1. The waste ternary 811 type battery is discharged in a battery testing cabinet to <3.0V, crushed with electricity, cracked under a nitrogen atmosphere at 550°C, and sorted by air flow, gravity, and light to obtain a crude black powder, and then demagnetized and impurities are removed. The crude black powder in this step includes ternary positive electrode material raw materials, negative electrode material graphite, and copper and aluminum impurities;
[0070] S2. The mixture after demagnetization and impurity removal is leached at 80° C. for 4 h using a mixture of ammonia water and hydrogen peroxide, wherein the mass ratio of ammonia water, black powder and hydrogen peroxide is 0.3:1:0.1, wherein the concentration of ammonia water is 12%, and then the mixture is separated by filter pressing to obtain a first black powder residue and a first filtrate;
[0071] S3. The first filtrate is heated at 105°C for 2h to form copper hydroxide precipitation, and the volatilized ammonia is condensed through an ammonia absorption tower and absorbed by pure water to 12% to obtain recovered ammonia, which is then added as a raw material to step S2 for recycling;
[0072] The hydrogen peroxide and the first black powder filter residue are mixed in a mass ratio of 0.2:1, heated to 80° C., and 20% oxalic acid is added to adjust the pH to 3.5, leached, and then filtered to obtain a second black powder filter residue and a second filtrate;
[0073] S4. Add 32% sodium hydroxide solution to the second filtrate to adjust the pH to 12, and precipitate aluminum, calcium and magnesium hydroxides;
[0074] Lithium hydroxide and aluminum hydroxide colloid are added to the second black powder filter residue to obtain a mixed material, so that the molar ratio of the sum of the molar amounts of manganese, cobalt and nickel in the mixed material to the lithium source and aluminum hydroxide colloid is 1:1.05:0.01, the mixed material is added as a ball milling medium for wet grinding, the solid content is 50%, the ball milling time is 3 hours, the particle size D50 of the mixed material after ball milling is 1.0-2.0μm, the material after ball milling is spray dried, the spray drying temperature is 200°C, the particle size D50 of the mixed material after spray drying is 5μm, the dried material is calcined, the calcination atmosphere is oxygen, the calcination temperature is 800°C, the calcination time is 13h, the air intake pressure is 0.3MPa, and then it is air flow crushed to obtain the alumina-coated ternary positive electrode material (NCM).
[0075] Comparative Example 1
[0076] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries, wherein the other steps are the same as those in Example 1, except that sulfuric acid of equal concentration is used instead of citric acid.
[0077] Comparative Example 2
[0078] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries, wherein the other steps are the same as those in Example 1, except that, in step S3, the pH value is adjusted to 1.0.
[0079] Comparative Example 3
[0080] A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries, wherein the other steps are the same as those in Example 1, except that, in step S4, the pH value is adjusted to 6.0.
[0081] Evaluation Test
[0082] The recovery rate test and electrochemical performance test were carried out on Examples 1-4 and Comparative Examples 1-3. The electrochemical performance test method is as follows: stir the slurry containing 90% positive electrode material, 5% acetylene black and 5% polyvinylidene fluoride (PVDF) by mass ratio, wherein the solvent is N-methylpyrrolidone (NMP). Apply evenly on a round aluminum foil with a diameter of 12 mm, pre-dry at 80°C for 2 hours, press into sheets, and then vacuum dry for 12 hours. The prepared electrode sheet is used as the positive electrode, the negative electrode is metallic lithium, the diaphragm is a porous polypropylene film (Celgard2500), and the electrolyte is 1 mol / L LiPF 6 The solution was assembled into a CR2032 button cell. Cyclic charge and discharge tests were performed on a multi-channel battery test system (LANDCTR2001A, Wuhan, China) with a voltage range of 2.8 to 4.3 V. The results are shown in Table 1.
[0083]
[0084]
[0085] The above results show that the change of acid between Examples 1-3 and the comparative example will affect the recovery rate and impurity effects. After the organic acid used for recovery is changed to inorganic sulfuric acid, the nickel, cobalt, manganese and lithium in the black powder will dissolve into the filtrate 2, resulting in a low recovery rate. The pH value of the organic acid used for recovery is high. When the pH value reaches 6, impurities such as aluminum, calcium and magnesium cannot be completely washed into the filtrate 2, resulting in excessive aluminum, calcium and magnesium impurities in the final product.
[0086] The alumina-coated ternary positive electrode material obtained in the present application has few impurities and can effectively remove impurity elements such as copper, aluminum, and magnesium, so that the purity of the product raw material is high. The selection of the leaching solution in step S2 and step S3 and the limitation of the leaching conditions are also beneficial to the high recovery rate and low loss of the raw materials of nickel, cobalt, and manganese of the ternary positive electrode material in the present application, providing a good foundation for the stability of the subsequent preparation of the alumina-coated ternary positive electrode material.
[0087] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing an alumina-coated ternary positive electrode material from waste ternary batteries, characterized in that: The following steps are involved: S1. Discharge, crush, crack and sort the used ternary batteries to obtain crude black powder, and then remove magnetism and impurities; S2. Leaching the demagnetized and impurity-removed crude black powder using a mixture of aqueous ammonia and hydrogen peroxide, and then performing filter press separation to obtain a first black powder residue and a first filtrate; S3. heating the first filtrate, evaporating and deammoniating to obtain recovered ammonia water and copper hydroxide, and adding the recovered ammonia water as a raw material to step S2 for recycling; leaching the first black powder residue with a mixture of hydrogen peroxide and an organic acid at a pH value of 3-4, and then performing filter press separation to obtain a second black powder residue and a second filtrate; S4. Add an alkaline solution to the second filtrate to precipitate aluminum, calcium and magnesium hydroxides; add a lithium source and aluminum hydroxide colloid to the second black powder residue to obtain a mixed material, so that the molar ratio of the sum of the molar amounts of manganese, cobalt and nickel in the mixed material to the lithium source and aluminum hydroxide colloid is 1: (1.05-1.06): (0.01-0.02), and the mixed material is spray-dried, calcined and air-flow-pulverized after ball milling to obtain an alumina-coated ternary positive electrode material; in step S2, the leaching temperature is 80-100°C and the leaching time is 4-8h; in step S3, the organic acid is one or more of acetic acid, citric acid, tartaric acid, oxalic acid, malic acid, ascorbic acid benzoic acid, salicylic acid and caffeic acid.
2. The method for preparing alumina-coated ternary positive electrode materials from waste ternary batteries according to claim 1, characterized in that: In step S4, the ball milling is wet milling, the ball milling medium is one or more of anhydrous ethanol and methanol, the ball milling time is 1-3 hours, and the particle size D50 of the mixed material after ball milling is 1.0-3.0 μm.
3. The method for preparing alumina-coated ternary positive electrode materials from waste ternary batteries according to claim 1, characterized in that: In step S4, the spray drying temperature is 180-220°C, and the particle size D50 of the mixed material after spray drying is 5-20 μm.
4. The method for preparing alumina-coated ternary positive electrode materials from waste ternary batteries according to claim 1, characterized in that: In step S4, the calcination conditions are as follows: the calcination atmosphere is oxygen or air, the calcination temperature is 750-900° C., and the calcination time is 6-13 hours.
5. The method for preparing alumina-coated ternary positive electrode materials from waste ternary batteries according to claim 1, characterized in that: In step S2, the mass ratio of ammonia water, black powder and hydrogen peroxide is (0.2-0.4):1:(0.1-0.2), wherein the concentration of ammonia water is 10-16%.
6. The method for preparing alumina-coated ternary positive electrode materials from waste ternary batteries according to claim 1, characterized in that: In step S4, the lithium source is one or more of lithium hydroxide and lithium carbonate.
7. The method for preparing alumina-coated ternary positive electrode materials from waste ternary batteries according to claim 1, characterized in that: In step S1, the cracking temperature is 500-600°C, and the cracking atmosphere is a nitrogen atmosphere.
8. An alumina-coated ternary positive electrode material prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing high-nickel lithium nickel cobalt aluminum oxide ternary electrode material by using screws
CN108306017A
Method for synthesizing cobalt oxalate dehydrate from waste lithium battery positive electrode active material leaching solution
CN112142589A